The ultraviolet upturn in field luminous red galaxies at 0.3 < z < 0.7. Issue 1 (8th March 2022) - De Propris, R; Ali, S S; Chung, C; Bremer, M N; Phillipps, S
ABSTRACT: We derive the evolution of the ultraviolet upturn colour from a sample of field luminous red galaxies at 0.3 < z < 0.7 with −24 < Mr < −21.5. No individual objects are securely detected, so we stack several hundred galaxies within absolute magnitude and redshift intervals. We find that the colour of the ultraviolet upturn (in observed NUV − i which is approximately equivalent to the classical FUV − V at the redshifts of our targets) does not change strongly with redshift to z = 0.7. This behaviour is similar to that observed in cluster ellipticals over this same mass range and at similar redshifts, and we speculate that the processes involved in the origin of the UV upturn are the same. The observations are most consistent with spectral synthesis models containing a fraction of a helium rich stellar population with abundances between 37 per cent and 42 per cent, although we cannot formally exclude a contribution due to residual star formation at the 0.5 per cent level (however, this appears unlikely for cluster galaxies that are believed to be more quenched). This suggests that the ultraviolet upturn is a primordial characteristic of early-type galaxies at all redshifts and that an unexpected nucleosynthesis channel may lead to nearly complete chemical evolution at early times.